Performance, carcass characteristics and gain cost of feedlot cattle fed a high level of concentrate and different feed additives - Rodrigues, Érico [UNESP]; Arrigoni, Mario de Beni [UNESP]; Andrade, Cláudia Regina Mendonça; Martins, Cyntia Ludovico [UNESP]; Millen, Danilo Domingues [UNESP]; Parra, Fernando Salvador; Jorge, Andre Mendes [UNESP]; Andrighetto, Cristiana [UNESP] (Sociedade Brasileira de Zootecnia, 2013)
The objective of this study was to evaluate the effects of feeding cattle with isoprotein and isoenergetic diets, with and without the addition of polyclonal antibody preparation (PAP), yeasts (YST) or monensin sodium (MON) on performance, carcass characteristics and gain cost in feedlot. Ninety-five 20-month old bullocks (323.3±21.8 kg) were distributed in 25 pens. The completely randomized experimental design had a 2 × 2 + 1 factorial arrangement and the treatments were replicated 5 times. There was no effect of MON for DMI throughout the feedlot period; however, MON reduced the dry matter intake (DMI) in g/kg of BW in the first 28 days when compared with the other treatments. The gain cost decreased with MON addition in relation to the other treatments. Inclusion of YST decreased average daily gain (ADG), final body weight, hot carcass weight, carcass weight, gain to feed ratio and DMI in g/kg body weight, worsening feed conversion and increasing the gain cost in the feeding periods. Inclusion of PAP increased ADG and decreased the gain cost, besides improving feed conversion. For MON and PAP, a difference was found for kidney-pelvic fat and kidney-pelvic fat per 100 kg of hot carcass weight. For MON and YST, there was a difference in ADG, feed conversion, gain cost and carcass yield and kidney-pelvic fat per 100 kg of hot carcass. Treatment YST worsened performance in relation to the non-supplemented treatments. Feeding PAP to animals did not influence performance and carcass characteristics of bullocks in feedlot negatively. Thus, PAP shows potential to substitute MON in cattle feeding using isoprotein and isoenergetic diets.
Keywords: cost; feedlot; monensin; polyclonal antibody preparation; yeasts